Phylogenetic and Evolutionary Analysis Reveals the Recent Dominance of Ciprofloxacin-Resistant Shigella sonnei and Local Persistence of S. flexneri Clones in India - Dhiviya Prabaa Muthuirulandi Sethuvel (American Society for Microbiology, 2020)
ABSTRACT Shigella is the second leading cause of bacterial diarrhea worldwide. Recently, Shigella sonnei seems to be replacing Shigella flexneri in low- and middle-income countries undergoing economic development. Despite this, studies focusing on these species at the genomic level remain largely unexplored. Here, we compared the genome sequences of S. flexneri and S. sonnei isolates from India with the publicly available genomes of global strains. Our analysis provides evidence for the long-term persistence of all phylogenetic groups (PGs) of S. flexneri and the recent dominance of the ciprofloxacin-resistant S. sonnei lineage in India. Within S. flexneri PGs, the majority of the study isolates belonged to PG3 within the predominance of serotype 2. For S. sonnei, the current pandemic involves globally distributed multidrug-resistant (MDR) clones that belong to Central Asia lineage III. The presence of such epidemiologically dominant lineages in association with stable antimicrobial resistance (AMR) determinants results in successful survival in the community. IMPORTANCE Shigella is the second leading cause of bacterial diarrhea worldwide. This has been categorized as a priority pathogen among enteric bacteria by the Global Antimicrobial Resistance Surveillance System (GLASS) of the World Health Organization (WHO). Recently, S. sonnei seems to be replacing S. flexneri in low- and middle-income countries undergoing economic development. Antimicrobial resistance in S. flexneri and S. sonnei is a growing international concern, specifically with the international dominance of the multidrug-resistant (MDR) lineage. Genomic studies focusing on S. flexneri and S. sonnei in India remain largely unexplored. This study provides information on the introduction and expansion of drug-resistant Shigella strains in India for the first time by comparing the genome sequences of S. flexneri and S. sonnei isolates from India with the publicly available genomes of global strains. The study discusses the key differences between the two dominant species of Shigella at the genomic level to understand the evolutionary trends and genome dynamics of emerging and existing resistance clones. The present work demonstrates evidence for the long-term persistence of all PGs of S. flexneri and the recent dominance of a ciprofloxacin-resistant S. sonnei lineage in India.